2021
DOI: 10.1128/spectrum.01736-21
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Therapy for the Prevention and Treatment of Fracture-Related Infection Caused by Staphylococcus aureus: a Preclinical Study

Abstract: Because of the growing spread of antimicrobial resistance, the use of alternative prevention and treatment strategies is gaining interest. Although the therapeutic potential of bacteriophages has been demonstrated in a number of case reports and series over the past decade, many unanswered questions remain regarding the optimal application protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Basic phage research and its applications are intensively pursued worldwide ( 1 ). For the nontraditional treatment of infections caused by Staphylococcus aureus strains, which belongs to the ESKAPE pathogen group with increasing multidrug resistance ( 2 ), the most convenient phages for therapeutic application are lytic bacteriophages of the genus Kayvirus ( 3 6 ). These bacteriophages are effective therapeutic agents for the treatment of severe infections with multidrug-resistant staphylococci ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Basic phage research and its applications are intensively pursued worldwide ( 1 ). For the nontraditional treatment of infections caused by Staphylococcus aureus strains, which belongs to the ESKAPE pathogen group with increasing multidrug resistance ( 2 ), the most convenient phages for therapeutic application are lytic bacteriophages of the genus Kayvirus ( 3 6 ). These bacteriophages are effective therapeutic agents for the treatment of severe infections with multidrug-resistant staphylococci ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a potential antibacterial agent, phages can effectively and specifically infect host bacteria ( Onsea et al., 2021 ). Nonetheless, phages often have distinct biological characteristics such as host range, proliferation rates, temperature and pH stability, which altogether limit the industrial production of phage preparations ( Cai et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations into the use of phage therapy for musculoskeletal infections are sparse; most of the knowledge coming from the Eliava Institute of Bacteriophages, Microbiology and Virology (Tbilisi, Georgia). Metsemakers is involved in multiple research projects on the topic of implant-related infections and reported a rising number of studies/instances in recent years [ 18 , 19 , 20 ]. They are the head of the care program for musculoskeletal infections and of the Coordination Group for Bacteriophage Therapy, Leuven, affiliated with Leuven University Hospitals.…”
Section: Scientific Sessionsmentioning
confidence: 99%